Manajemen Sarana dan Prasarana di Pondok Pesantren Zulhijjah Batanghari pada Masa Pandemi Covid-19 - Mukhlis; A. Khalik; Zainudin (JMiE (Journal of Management in Education), 2022)
This study aims to describe the management of facilities and infrastructure at the Zulhijjah Islamic Boarding School, Batang Hari Regency during the Covid-19 pandemic. This research uses qualitative approaches and research methods. The setting of this study is the zulhijjah islamic boarding school and the subjects of this study are santri and ustad / ustazah. The methods used are observation, interview, and documentation. Data validity using data types and data sources. The results of this study show that the Zulhijjah Islamic Boarding School has carried out steps to manage facilities and infrastructure; 1) Zulhijjah Islamic Boarding School conducts planning by recording the needs and provision of funds, 2) procurement of infrastructure according to the needs of the Islamic boarding school, 3) inventory is a recording of existing facilities and infrastructure in the Pesantren with details of the number and condition of goods in the Zulhijjah Islamic Boarding School, 4) maintenance of infrastructure as a whole, 5) elimination of facilities and infrastructure for damaged goods, and it is not worth using again according to the procedure of mutual agreement first.